Mapping the research activities on social accountability in health of an emerging international community - Dubé, Tim; Beaulieu, Marie-Dominique; Fourati, Mariem; Benaskeur, Imane (Canadian Medical Education Journal, 2023)
Implication Statement We used environmental analysis to document the nature and characteristics of research on social accountability (SA) in health conducted by members of an emerging international Francophone network on SA. We developed a questionnaire focusing on research inputs, activities, and outputs, which could serve as a reference in other institutions and networks. The results provide a better understanding of SA research within the international Francophone community. Networks that aim to promote research among their members should carry out such mapping to leverage the strengths of the community and act as catalysts and stepping stones for future research.